Pressure Wave Interaction with Fractured Porous Zone in Porous Medium - A. A. Gubaidullin; O. Yu. Boldyreva; D. N. Dudko (Учёные записки Казанского университета: Серия Физико-математические науки)
The propagation of a pressure wave in a porous medium with a fractured porous zone was numerically investigated. The study used a two-velocity model of a porous medium and a three-velocity model of a fractured porous medium. The problem was examined in a twodimensional formulation, considering cases when a porous medium has a free surface or is unbounded. The fractured porous zone was shown to have either an ellipseor rectangle-shaped boundary. The inﬂuence of such inhomogeneities on the propagation of pressure perturbations was analyzed.